SYNTHESIS OF NANOCRYTALLINE (alpha)-Fe2O3/ZEOLITE COMPOSITE USING SPRAY PYROLYSIS METHOD FOR CATALYTIC AQUATHERMOLYSIS - RUSTANDI (NIM : 20210023); Tim Pembimbing : Prof. Dr. Eng. Khairurrijal, Dr. Eng. Ferry Iskand, AGUS
Nanocrystalline α-Fe2O3/zeolite composite has been synthesized by a spray pyrolysis method. As raw material, FeCl3.6H2O, NaOH and natural zeolite (clinoptilolite) were used with ratio of mass 2,25:1:1. In this method, the droplets from solution precursors were generated by a ultrasonic nebulizer and carried by a gas carrier at 3 liter per minute to a tubular furnace which have 100 cm of length (effective length 50 cm) and 3 cm of diameter. The temperatur of the tubular furnace was maintain ed from 700oC to 900oC. In this tubular furnace, solvent of droplet was evaporated and the particle of solute was diffuse in droplet. After that, the droplet was dried, precipitated, and then reacted at pyrolysis to formed particle (powder). The powder was collected using a bag filter. Morphological, structural and chemical analyses of powders were characterized using scanning electron microscopy (SEM), X-ray powder diffraction (XRD) and energy dispersive X-ray spectroscopy (EDS), respectively. From the XRD analysis, the peaks of NaCl and α-Fe2O3 crystal were observed clearly at powder which synthesized at 900 0C, but there was no a peak of zeolite crystal. Using Scherrer method, the crystallite size of α-Fe2O3 was calculated and it was found around 67 nm. From the SEM image observation, the prepared particles have a spherical shape, non aglomerated with average particle size 533 nm. From the EDS results, it was found that the powders contained Al, C, Cl, Fe, Na, O and Si elements, indicating the presence of zeolite element in the powders. The catalytic acitivity of this composite on aquathermolysis has been tested using autoclave at 120oC for 6 hours. As result, the catalytic activities of this composite was better than α-Fe2O3 material.